Analisis Alur dan Sudut Pandang dalam Cerpen Percayakah Kau Padaku - Indah Tri Susanti; Inez Khansa Monica; Shafa Aura Anindya; Mohamad Afrizal (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the plot and point of view in the short story Percayakah Kau Padaku, a work that features deep psychological exploration and strong emotional conflict. Using a structuralist approach, this research evaluates how the non-linear plot and the choice of first-person perspective influence the reader's understanding of the characters and the main themes, namely trust and betrayal. The complex plot, with shifts between the past and present, creates tension and adds depth to the protagonist's inner journey. On the other hand, the first-person perspective allows the reader to directly experience the psychological dilemmas faced by the character, enriching the understanding of the internal conflict. Through this analysis, it can be concluded that the plot and point of view serve as tools to deepen the characters, strengthen the themes of the story, and provide a more intense reading experience. This study also offers suggestions for further story development by enriching the supporting characters and clarifying the time transitions in the plot.